EFEKTIVITAS PENERAPAN METODE REWARD AND PUNISHMENT PADA PEMBELAJARAN FIQIH DALAM MENINGKATKAN ANTUSIASME BELAJAR SISWA KELAS X SEKOLAH MENENGAH KEJURUAN DARUN NAIM BEKASI - Fahmi, Ahmad; Sitika, Ahmad Junaedi; Syarief, Ceceng (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2024)
Rewards will make students study actively, the application of the reward and punishment method should be able to make students motivated to study Islam, not violate school rules and be expected to behave well towards everyone, not focus on studying, lazy to do assignments, not pay attention to the teacher, have difficulty understand the lesson and get bored of taking the lesson. This research approach is qualitative. Data collection is carried out using observation, interviews and documentation. The results of the research show that the application of the reward and punishment method is effective in increasing enthusiasm for learning PAI fiqh in class X students at Darun Naim Vocational School, Bekasi. By giving rewards and punishments, students can improve, study diligently, always follow the PAI fiqh learning process, always carry out assignments given by teachers, and obey school rules and regulations. So that the presence of rewards and punishments can make students better, besides that the development of students' learning motivation is quite good and effective. With this, they can increase their enthusiasm to do several good things that can make them achieve, which in the future will make them passionate about learning and always enthusiastic. The implications of this research activity include: 1) developing more effective learning strategies, 2) strengthening learning discipline, and 3) improving the reward and punishment system.